Tres epigramas griegos inéditos del humanista Juan de Verzosa: una aportación a la historia de la Anthologia Graeca - Pino González, Eduardo del, 1966- (2021)
En la Collectio Vulcaniana de la Bibliotheek Universiteit Leiden (Vul. 103 I, f. 2v) se conservan tres epigramas griegos inéditos del humanista hispano-latino Juan de Verzosa. Fueron escritos en Lovaina con motivo de la muerte, en 1545, del profesor de griego Rutgerus Rescius. La aparición de los textos aporta más luz al periodo docente del joven Juan de Verzosa en la lengua griega, así como a la historia de la Anthologia Graeca.
There are three unedited Greek epigrams written by the Spanish humanist Juan de Verzosa in the Collectio Vulcaniana of the Bibliotheek Universiteit Leiden. He composed them in Louvain after the death of the Greek professor Rutgerus Rescius. This discovery enlightens Verzosa’s docent stay in Louvain. It adds as well a note to the history of the Anthologia Graeca.
Keywords: Verzosa, Juan de, -- 1523-1574; Epigramas; Literatura griega